Mid-term results of mitral valve repair using flexible bands versus complete rings in patients with degenerative mitral valve disease: a prospective, randomized study - Alexandr V. Bogachev-Prokophiev; Alexandr V. Afanasyev; Sergei I. Zheleznev; Vladimir M. Nazarov; Ravil M. Sharifulin; Alexandr M. Karaskov (Journal of Cardiothoracic Surgery, 2017)
Abstract Background We aimed to compare the outcomes of mitral valve repair with flexible band (FB) versus complete semirigid ring (SR) in degenerative mitral valve disease patients. Methods From September 2011 to 2014, 171 patients were randomized and underwent successful mitral valve repair using a SR (n = 85) or FB (n = 86). There were no significant between-group differences at baseline. Results There were no early mortalities. The mean follow up was 24.7 months. The 2-year survival was 96.0 ± 2.3% (95% confidence interval [CI], 88.6–98.7%) and 94.3 ± 2.8% (95% CI, 85.5–97.9%) in the SR and FB groups, respectively (p = 0.899). The left ventricle remodeling was similar between the groups. Higher transmitral peak (8.5 [3.9–17] vs. 6 [2.1–18] mmHg, p < 0.001), mean pressure gradients (3.7 [1.3–8] vs. 2.8 [0.6–6.8] mmHg, p = 0.001), and systolic pulmonary artery pressure (34.5 [20–68] vs. 29.5 [8–48] mmHg, p < 0.001) was observed in the SR group. The 2-year freedom from recurrence of significant mitral regurgitation was significantly higher in the FB group than the SR group (p = 0.002). Residual mitral regurgitation was an independent prognostic factor of recurrence of mitral regurgitation. The 3-year freedom from reoperation was significantly higher in the FB group than the SR group (p = 0.044). Conclusion Patients with degenerative mitral valve disease may benefit from valve repair with FBs. Residual mitral regurgitation before discharge is an independent risk factor of late insufficiency recurrence. Trial registration ClinicalTrials.gov NCT03278574 , retrospectively registered on 06.09.2017.